Algorithm of numerical modelling of the surface diffusion flow for periodic triangulated surfaces - Efremenko, Yury D. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2022)
The algorithm of numerical modelling of the surface diffusion flow for periodic triangulated initial surface is proposed in the paper. To process the singularities that appear during computations the algorithms of retriangulation were developed. The cases of singularity inside of the cube containing the surface, on it’s face, edge and corner were considered. The work of the algorithm is illustrated with several examples.